Development of a hybrid CFD-PBPK model to predict the transport of xenon gas around a human respiratory system to systemic regions. Issue 4 (April 2019) - Haghnegahdar, Ahmadreza; Zhao, Jianan; Kozak, Max; Williamson, Patrick; Feng, Yu
Abstract: Administering incorrect doses of conventional anesthetic agents through the pulmonary route can cause potential health risks such as blood coagulation, platelet dysfunction, and deteriorating organ function. As an alternative, xenon can minimize the impact on the cardiovascular system and provide the neuroprotective effect, hemodynamic stability, and fast recovery. However, the inhalation pattern still needs to be carefully monitored and controlled to avoid health risks caused by over administering xenon to patients during unconsciousness. Thus, high-resolution lung absorption and whole-body translocation data are critically needed to fully understand how to administer the gas and coordinate with the patient to accurately control the dose. Clinical studies are not able to provide accurate dosimetry data due to their limited operational flexibility and imaging resolution. Therefore, a computational fluid dynamics (CFD) model was employed in this study to simulate the transport and absorption of the inhaled xenon which is connected with a physiologically based pharmacokinetic (PBPK) model to predict the translocation into the systemic regions. To study the effects of different breathing patterns on xenon transport dynamics in the human body, a realistic breathing waveform and two steady-state flow rates with inhalation durations of 2 and 1.5 seconds were selected. For the realistic breathing cycle, the inhalation-exhalation periods are defined for a human at rest and the other two cases have a fixed volumetric flow rate of 15 L/min. As the two latter cases only simulate the inspiratory phase, a 1-second holding time was applied to represent the missing periods of the full breathing time. Simulations were performed in a subject-specific human upper airway configuration from mouth to G6. Numerical results show that with the accurate lung uptake predictions obtained from the CFD model, the hybrid CFD-PBPK model with TRANSIT compartments generates more precise and breath-specific trends compared to simple PBPK models. Numerical results demonstrate that breathing pattern can significantly influence the xenon uptake in the human body, which can be utilized as a critical factor to be coordinated by clinicians to achieve the optimized xenon dose. Furthermore, parametric analyses were performed for the influence of breathing patterns on local airflow distributions, gas species translocations, and lung elimination mechanisms followed by species diffusion into the systemic regions.